2023
DOI: 10.1155/2023/1875253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Virulence Factors in Salmonella serovars Isolated from Poultry and Human Samples

Abstract: Salmonellosis is a common infectious disease in humans caused by Salmonella spp., which in recent years has shown an increase in its incidence, with products of avian origin being a common source of transmission. To present a successful infective cycle, there are molecular mechanisms such as virulence factors that provide characteristics that facilitate survival, colonization, and damage to the host. According to this, the study aims to characterize the virulence factors of Salmonella spp. strains isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In the current study, 100% of strains carried the genes invA and hilA, 92.2% harbored the fimA gene, and 90.2% carried the spvB gene. Our findings demonstrate the potential pathogenicity of the S. Enteritidis strains isolated from human and non-human sources, which is in line with what has already been described by other authors [56][57][58].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, 100% of strains carried the genes invA and hilA, 92.2% harbored the fimA gene, and 90.2% carried the spvB gene. Our findings demonstrate the potential pathogenicity of the S. Enteritidis strains isolated from human and non-human sources, which is in line with what has already been described by other authors [56][57][58].…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy underscores the presence of resistant bacteria across food, animals, and humans. Lozano-Villegas et al [45] suggested that the variation in Salmonella strains isolated from broilers and humans could be attributed to differences in pathogenic potential, influenced by the type and number of detected virulence genes, including those linked to antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction was carried out using a DNA extraction kit, following the manufacturer's instructions (AddBio Incorporated Limited, Daejeon, Republic of Korea). Table 4 lists the primers used for detecting Salmonella enterica serovars and ESBL-resistance genes as previously reported [74,[77][78][79].…”
Section: Identification Of S Enterica Serovars and Detection Of Esbl-...mentioning
confidence: 99%